Quantitative Electrochromatography of Uranium and Platinum on Papers Impregnated with Thorium and Antimony Based Cation Exchanger - K. Misra, Aditya (Asian Journal of Chemistry, 2010)
Electrochromatography of 32 metal ions have been studied on papers impregnated with thorium antimonate cation exchanger in aq. organic acids, aq. nitric acid as well as in EDTA buffers. On the basis of differential migration which depends on the ion exchange properties of thorium antimonate and nature of complexes formed with the electrolytes, some useful qualitative and quantitative separations of synthetic mixtures of metal ions have been achieved. The effect of some other physical parameter has also been discussed. Quantitative separation of platinum and uranium has been developed.